ANÁLISE DO MERCADO DE PISOS DE MADEIRA LAMINADA NA CIDADE DE CURITIBA (MARKETING DE VENDAS AO CONSUMIDOR FINAL) - Polzl, Willian Borelli; da Silva, João Carlos Garzel Leodoro (Floresta, 2001)
O crescente aumento da oferta de pisos de madeira deve vir seguida do uso de instrumentos de marketing, desta forma minimizando os efeitos da concorrência por meio da diferenciação de produtos e serviços. Esta pode utilizar diferentes artifícios que permitam agregar outros valores além dos encontrados nos produto. A análise de mercado aqui apresentada está baseada no Composto de Marketing (produto, preço, promoção e distribuição). Com este ponto de vista pode-se distinguir segmentações de mercado quanto a produto, preço e serviços. Mostrando detalhes que podem ser repensados pelas empresas do ramo. ANALYSIS OF WOOD FLOOR MARKET IN CURITIBA (MARKETING MIX TO SALES TO FINAL CONSUMER) Abstract The incrase in wood floor supply must be followed to by marketing tools, In order to minimize the effects of competition through differentiation of products and services. Retail shops can use alternative ways to add value in their products. This paper made an market analysis using the marketing mix concept (price, product, place and promotion). This concept recommends to look the markets components and actors’ interaction with respect to any product, pricing, services included, distibution details, sales promotion, payment advantages, time of delivery, professional order, etc. Showing details that give clues and insights for rethinking companies strategies in the same line (wood floor shop).